[tex] \huge\mathtt{Direction}[/tex]
Write expanded form of each exponential expression then solve for the value.
1). 3³ + 2⁵
[tex] \large\mathtt{Expanded \: Form}[/tex]
- (3 x 3 x 3) + (2 x 2 x 2 x 2 x 2) = 27 + 32 = 59
2). 2⁶ + 4²
[tex] \large\mathtt{Expanded \: Form}[/tex]
- (2 x 2 x 2 x 2 x 2 x 2) + (4 x 4) = 64 + 16 = 80
3). 3² x 5²
[tex] \large\mathtt{Expanded \: Form}[/tex]
- (3 x 3) x (5 x 5) = 9 x 25 = 225
4). 5³ x 2⁸
[tex] \large\mathtt{Expanded \: Form}[/tex]
- (5 x 5 x 5) x (2 x 2 x 2 x 2l x 2 x 2 x 2 x 2) = 125 x 256 = 32,000
5). 6³ - 3⁴
[tex] \large\mathtt{Expanded \: Form}[/tex]
- (6 x 6 x 6) - (3 x 3 x 3 x 3) = 216 - 81 = 135